Analytical model for coupled consolidation and diffusion of organic contaminant transport in triple landfill liners. Issue 2 (April 2021) - Yan, Huaxiang; Wu, Jiawei; Thomas, Hywel R.; Ding, Hao; Zhan, Liangtong; Xie, Haijian
Abstract: A triple-layer composite liner consisting of a geomembrane liner (GMB), a geosynthetic clay liner (GCL) and a compacted clay liner (CCL) is commonly used at the landfill bottom liner system to isolate the contaminated leachates. In this paper, one-dimensional quasi-steady-state small deformation model (SDSS) was developed to investigate the behavior of organic chemicals transport in landfill composite liner system considering coupled effect of consolidation, diffusion and degradation. The first and second type bottom boundary conditions are used to derive the analytical solutions. The generalized integral transform technique (GITT) is adopted to derive the analytical solutions. The effect of consolidation on the performance of GMB/GCL/CCL with intact or leaking GMB is investigated. The triple liner under double drainage boundary condition (DDBC) has better performance compared to the case under single drainage boundary condition (SDBC). This is because the velocity induced by consolidation under DDBC is lower than that under SDBC. The effect of GCL consolidation shows an opposite trend compared to CCL consolidation. Considering GCL consolidation can increase the breakthrough time. The effective diffusion coefficient of GCL can be two magnitude orders smaller after consolidation, which provides a better diffusion barrier for the chemical transport. The effects of adsorption and degradation have been analyzed as well. Increasing the adsorption capacity of a deforming composite liner can increase the steady-state bottom flux, which shows the opposite tendency compared to the case without considering consolidation. This is due to the fact that for the case of a deforming composite liner, the advection induced by consolidation includes a new term due to the solid velocity. This velocity will result in the increase the mass of chemical migration through the composite liner.